2020
DOI: 10.1002/elan.202060110
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots Integrated NiCo2O4 Hierarchical Nanoneedle Arrays Supported on Ni Foam as Efficient and Stable Electrode for Hydrogen and Oxygen Evolution Reactions

Abstract: The production of hydrogen and oxygen via water electrolysis has become a sustainable and encouraging pathway for the establishment of new energy sources. Herein, we report the successful growth of hierarchical NiCo2O4‐carbon dots (CDs) nanoneedle arrays supported on nickel foam through a simple and environmentally benign hydrothermal self‐assembly technique. The designed material acts as a binder free electrode and shows bifunctional electrocatalytic activity for both hydrogen evolution reaction (HER) as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Hydrogen (H 2 ) fuel has the potential to replace fossil fuel because it is environmentally benign and large amount can easily be obtained from water [1][2][3][4]. Electrochemical water-splitting is one of the most effective and efficient techniques employed for H 2 and oxygen (O 2 ) productions via processes: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) [5][6][7]. Commercial water electrolyzer is used to produce H 2 , which is employed as the major fuel for alternative future energy source, mainly performed in alkaline media [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen (H 2 ) fuel has the potential to replace fossil fuel because it is environmentally benign and large amount can easily be obtained from water [1][2][3][4]. Electrochemical water-splitting is one of the most effective and efficient techniques employed for H 2 and oxygen (O 2 ) productions via processes: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) [5][6][7]. Commercial water electrolyzer is used to produce H 2 , which is employed as the major fuel for alternative future energy source, mainly performed in alkaline media [4].…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution TEM (HRTEM) image revealed that the lattice fringe is not clear enough, which indicates a relatively poor crystallinity characteristic of S-CDs core (Figure S1a). 32 The poor crystallinity of S-CDs was further confirmed by the selected area electron diffraction (SAED) patterns (Figure S1b). 33 Raman spectra reflected that the intensity ratio of the disordered D band at 1374 cm −1 and the crystalline G band at 1574 cm −1 (I G /I D ) was 0.89.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…This conformational change is favorable for molecular aggregation and a final emission enhancement (i.e., a light-controlled aggregation-induced phosphorescence (AIP) effect). Additionally, previous literature reported that CDs can be produced by the thermal pyrolysis of raw material in strongly alkaline environment and can be synthesized by hydrothermal treatment of polycarboxylic acid compound. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NiCo 2 O 4 (NC)-carbon dots (CDs) nano needle arrays have been fabricated on nickel (Ni) foam and directly used as an OER catalyst without any electrode binder [ 35 ]. Poly(vinyl pyrrolidone) were exposed to heat for 5 h at 180 °C to obtain CDs, and then different amount (5, 25 and 40 mg) of CDs were mixed with another couple of salts to generate the catalysts, and they were denoted as NCCD5, NCCD25 and NCCD40, respectively.…”
Section: Advanced Electrode Materials For Oermentioning
confidence: 99%